Role of microRNA in pathogenesis, diagnostics and therapy of cancer - Majorek, Karolina; Krzyżosiak, Włodzimierz J. (Contemporary Oncology/Współczesna Onkologia, 2006)
This article presents in brief some basic facts regarding biogenesis and physiological function of microRNAs, which are potent regulators of cell proliferation, differentiation, apoptosis, embryogenesis and organogenesis. The recently revealed links between microRNA dysfunction and human cancers are more extensively discussed, and some examples and perspectives of microRNA application in diagnostics, prognostics and therapy of cancer are presented. The postulated connection between germline mutations in microRNA genes and predisposition to cancer is also discussed.